Towards a sustainable European energy system: Linking optimization models with multi-regional input-output analysis. (November 2019) - Siala, K.; de la Rúa, C.; Lechón, Y.; Hamacher, T.
Abstract: The European Union set ambitious goals regarding renewable energy and greenhouse gas (GHG) emissions. This study uses two models to analyze the implications of these goals on the European energy system and on the rest of the world, based on several scenarios for the mid and long term. First, using a linear programming optimization model for capacity expansion and unit commitment, we obtain the optimal design of the European power system in 2030 and 2050. Results for Germany are then used as input in a Multi-Regional Input-Output Analysis with the objective of analyzing the environmental and socioeconomic effects derived from the new energy system. The linking of both models in each scenario is at the core of this study. Results show the capabilities of this method in terms of GHG emissions, cumulative energy demand, value added, and job creation. Highlights: We conduct an electricity system optimization for Europe for 2030 and 2050. We link the optimization model to a Multi-Regional Input-Output model. Environmental and socioeconomic impacts are derived for each scenario. Decarbonization leads to more jobs, more added value and less primary energy use.